Keratoconus Current and Future State-of-the-Art - Armia, Ashraf; Mazzotta, Cosimo; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book provides a practical guide to the most recent advances in the diagnostic management of corneal ectasia. Clear, concise chapters address new standardized nomograms of treatment of early progressive ectasia, new epithelium on future crosslinking with and without oxygen supplement, customized protocols, laser assisted corneal regularization protocols and the new femtolaser assisted lamellar corneal transplant. Clinicians and surgeons seeking a go-to guide on the topic of corneal ectasia will find this book to be an essential resource for the latest developments and predicted future trends in the field. .
Keratoconus imaging: current advances & broad horizons -- Pachymetry-Guided CXL and New Enhanced Epi-On CXL approaches -- Customized Surface Ablation Plus CXL -- CXL at the slit lamp and the Sub 400 protocol for thin corneas -- Corneal Allogenic Intrastromal Ring Segments - A Form of Mid- Peripheral Intra-Stromal Anterior Lamellar Keratoplasty.-Visual rehabilitation and keratocounus stability: Toric ICL, Toric IOL and the VIVA ICL for presbyopia.-The Tear Film and Ocular Surface Changes in Keratoconus -- Femto-DALK. .
Keywords: Ophthalmology; Ophthalmology; Keratoconus -- diagnosis; Keratoconus -- therapy